Unsettling Colonialism in the Canadian Criminal Justice System - Chartrand, Vicki; Savarese, Josephine (Athabasca University Press, 2023)
Canada's criminal justice system reinforces dominant relations of power and further entrenches the country in its colonial past. Through the mechanisms of surveillance, segregation, and containment, the criminal justice system ensures that Indigenous peoples remain in a state of economic deprivation, social isolation, and political subjection. By examining the ways in which the Canadian justice system continues to sanction overtly discriminatory and racist practices, the authors in this collection demonstrate clearly how historical patterns of privilege and domination are extended and reinforced.